PENGUJIAN USABILITY WEBSITE DOKUMENTASI MENGGUNAKAN SYSTEM USABILITY SCALE (SUS) - Fathiyah Nopriani; Muhammad, Maulana Asykari (Universitas Methodist Indonesia, 2024)
Documentation websites are a means for programmers to find solutions to the problems they face. Documentation websites that generally provide detailed information regarding how to use a particular framework. The documentation website used in this research is the documentation website from Tailwind CSS. Tailwind CSS is a CSS framework that has a utility-based component principle. With these principles, the website development process will be shorter, more flexible, responsive, and use code more efficiently. However, the convenience provided forces writing CSS code to be inline-CSS. This results in confusion arising from website programmers regarding CSS terms that are changed by Tailwind CSS. The Tailwind CSS website, which provides information related to the Tailwind CSS framework documentation, is in practice less intuitive, making it difficult for novice programmers to find solutions to the problems they face. This research aims to determine the usability of the Tailwind CSS website, from a student's perspective. The method used in this journal is SUS which is carried out by asking 10 questions related to the Tailwind CSS website to 30 respondents consisting of 87% men and 13% women. The selected respondents were students majoring in technology who used the documentation website from Tailwind CSS. The results of this research found that the Tailwind CSS website received a score of 70 on the SUS and could be categorized as Grade C or Fair.